1988
DOI: 10.1007/bf00314250
|View full text |Cite
|
Sign up to set email alerts
|

Generalized epileptic seizures as the presenting symptom of lacunar infarction in the brain

Abstract: Five elderly hypertensive patients presented with grand mal seizures and had computed tomographic (CT) findings consistent with lacunar infarction. Three of them had also a recent hemiparesis, contralateral to the side of the CT findings. Follow-up CT scans supported the diagnosis of lacunar infarction. Contrary to the accepted opinion, generalized epileptic seizures may be the presenting symptom of lacunar brain infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 20 publications
0
9
1
2
Order By: Relevance
“…In view of the controversial data in the literature [6,8,9], no patients with early-onset seizures are observed in our study. The time of occurrence of seizures in relation to the lacunar stroke(s) is highly variable and, on average, longer than for those in relation to territorial infarcts.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…In view of the controversial data in the literature [6,8,9], no patients with early-onset seizures are observed in our study. The time of occurrence of seizures in relation to the lacunar stroke(s) is highly variable and, on average, longer than for those in relation to territorial infarcts.…”
Section: Discussioncontrasting
confidence: 75%
“…While the risk factors for seizures related to territorial infarcts [4,5] are well known, the relation to lacunar infarcts remains uncertain [6][7][8][9]. Fisher [10] even considered his occurrence in a stroke patient as an exclusion criterion for the diagnosis of a lacunar infarct.…”
Section: Introductionmentioning
confidence: 97%
“…Epilepsia após AVC tem sido relacionada mais frequentemente a lesões do território carotídeo, tanto em estudo anatomopatológico 23 como clínico 7,25 . Numa revisão realizada por Shinton et al 25 não foi encontrado relato de epilepsia após AVC em pacientes com lesões restritas ao território vertebrobasilar; lesões profundas, sem comprometimento cortical, como causa de epilepsia, têm sido observadas ocasionalmente 20,25 e infartos lacunares são raramente referidos como etiologia de epilepsia 1,8,27 , sendo que o tamanho do infarto parece ter relação com crises epilépticas 12 . Os nossos achados foram, portanto, concordantes com a literatura, tendo sido o quadro clínico também indicativo de acometimento carotídeo nos pacientes do G1 11 .…”
Section: Discussionunclassified
“…The authors observed seizures in 18% of their 47 neuropathologically verified cases. In a more recent study of patients with MRI features of subcortical vascular en cephalopathy, subcortical lacunar lesions appeared to be associated with a significant risk for seizures [ 18], Rarely, lacunar infarctions may be associated with generalized tonic-clonic seizures [19]. In a systematic analysis of 118 patients with postthrombotic ischemia-related seizures, 5 patients (4.2%) presented with lacunar infarction on the CT; 4 out of those developed chronic epilepsy [20].…”
Section: Subcortical Infarctionmentioning
confidence: 99%